Parada cardiorrespiratória em ambiente pré-hospitalar: ocorrências atendidas pelo serviço de atendimentomóvel de urgência de Belo Horizonte - Daniela Aparecida Morais (2007)
The Mobile Emergence Service of Belo Horizonte (SAMU/BH), initiated in 2003, has trained staff members and ambulances equipped for pre hospital assistance. Among the most serious cases is the cardiorespiratory arrest. This study aims to analyze factors which influenced the assistance given to patients who had cardiorespiratoryarrest, in pre hospital environment of Advanced Support Units (ASU), in the city of Belo Horizonte, during 2005. To collect the data, we prepared an instrument containing Ustein style based variables. Statistical analysis such as associations, descriptive and space analysis were used to treat the data. Patients (n=1548) who had cardiorespiratory arrest were included. Space analysis of patients assisted in Belo Horizonte demonstrated lack of clusters. The majority had assistance during daytime, between Saturday and Tuesday, with a mean of 5 per day, and 129 per month.The majority (68.8%) were male, age ranging from 0 to 106 years, with a mean of 45 to 54 years old. The cardiorespiratory arrests were classified according to clinical and external causes. The majority presented clinical causes (62.2%). The ASU which assisted the patients in Belo Horizonte had a mean time-response of 10.3 minutes to arrive at the local, and of 18 minutes in other cities around. The majority of patients were already dead when the staff arrived. Cardiopulmonary resuscitation (CPR) wasdone on 351 patientes, and 33.3% presented ventricular fibrillation or tachycardia, without the presence of pulse on the first evaluation. Among these, 23.6% had immediate recovery and were taken to a hospital. The ambulance time-response, the CPR, and the cardiac rhythm were the factors that influenced immediate survival after CPR. Logistic regression, however, indicated only the CPR maneuver and the cardiac rhythm as significant. Patients who had CPR by the ASU and Mobile Emergency Service (SAMU/BH) teams had 2,8 more immediate survival chance andwho had cardiac rhythm such as asystolia showed 2.6 times less immediate survival chance. Other variables did not show association with immediate survival after CPR.Results showed the importance of SAMU in the assistance of patients who had cardiorespiratory arrest in the community.